POSISI DAN PERAN IBRAHIM MENURUT ISLAM - Mr Djam’annuri (Religi: Jurnal Studi Agama-agama, 2015)
Once a year, on the occasion of  celebrating the Feast of  Sacrifice (‘ Îd al-Adlhâ ) or at the time of Hajj, the Prophet Ibrahim as if “life” in the midst of  the Muslims through the repetition of a portion of  his life history. The recognition of the Muslims to the Prophet Ibrâhîm nearly as familiar with their recognition to the Prophet Muhammad. In Islam, he has a very important position and role. He is not only believed to be a prophet who has certain privileges, but also be a good example and model, especially in his obe- dience to Allah, his sincerity in religion, and his persistence in holding the principle of the oneness of Allah.However, the Qur’an, the main source of Islam, does not provide a detailed and chronological story about him but only a sort of fragments that could be considered off each other, but it all revolves around the fundamental religious attitude of Abraham as a Muslim, Hanîf, and away from polytheism. A detailed story of  Abraham is usually equipped with sources outside the Qur’an, both originating from Muslim writers or derived from sources that are usually refer red to Isrâîliyyât stories, including the stories of  Abraham contained in the Old Testament.